Clinical outcomes of arthroscopic stabilization procedures in patients with shoulder dislocation combined with posttraumatic adhesive capsulitis - Ji-Hyun Seo; Sang-Jin Shin (Clinics in Shoulder and Elbow, 2026)
Background: This study was conducted to analyze clinical outcomes after arthroscopic stabilization procedures in patients with shoulder instability and posttraumatic adhesive capsulitis. Methods: Patients who underwent arthroscopic Bankart repair between 2019 and 2022 with limitation of forward flexion